A note on the choice of the best selection criterion for the optimal regression model - Herzberg, Agnes M; Tsukanov, Alexander V. (Utilitas Mathematica, 1999)
A method for choosing the best selection criterion for the choice of regression model in the case of a small number of observations is discussed. A new integrated criterion, i.e. the regret of the minimum of possible average mean-squared errors of prediction, is used. This criterion uses simulation techniques and prior information about the experimental error variance and the limits of the independent variables.